2012
DOI: 10.1038/mi.2012.14
|View full text |Cite|
|
Sign up to set email alerts
|

Thymic stromal lymphopoietin (TSLP)-mediated dermal inflammation aggravates experimental asthma

Abstract: Individuals with one atopic disease are far more likely to develop a second. Approximately half of all atopic dermatitis (AD) patients subsequently develop asthma, particularly those with severe AD. This association, suggesting a role for AD as an entry point for subsequent allergic disease, is a phenomenon known as the ‘atopic march’. While the underlying cause of the atopic march remains unknown, recent evidence suggests a role for the cytokine TSLP. We have established a mouse model to determine whether TSL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 40 publications
(59 reference statements)
5
93
0
Order By: Relevance
“…TSLP binds to a receptor complex composed of an IL7Ra chain and a TSLP-specific TSLPR chain (2,3). TSLP has been associated with a wide range of immune responses, including allergic responses (4)(5)(6), but also CD8 + T cell responses such as those induced by influenza viruses (7).…”
mentioning
confidence: 99%
“…TSLP binds to a receptor complex composed of an IL7Ra chain and a TSLP-specific TSLPR chain (2,3). TSLP has been associated with a wide range of immune responses, including allergic responses (4)(5)(6), but also CD8 + T cell responses such as those induced by influenza viruses (7).…”
mentioning
confidence: 99%
“…Several models of induced TSLP expression in mouse keratinocytes result in subsequent allergic airway infl ammation following intranasal challenge, suggesting that TSLP may be an important factor contributing to this progression from AD to AR and asthma Demehri et al 2009 ;Leyva-Castillo et al 2012 ;Jiang et al 2012 ). Although many of these methods used to induce TSLP expression result in artificially high systemic levels of TSLP that are not seen in AD patients, we have found that intradermal administration of TSLP triggers progression from atopic dermatitis to asthma in the absence of systemic TSLP (Han et al 2012 ). In this study, TSLP was the airway response to antigen challenge was shown to be TSLP independent.…”
Section: Skin Disordersmentioning
confidence: 88%
“…Airway epithelial, dendritic, mast and mesenchymal cells as well as eosinophils represent the master mediators of TLR-associated aberrant immune responses leading to perpetuated Th2 inflammation, airway remodeling and constriction and consequently to airflow obstruction and decreased airway caliber (Phipps et al, 2007). Activation of TLRs by either bacterial (TLR2, TLR9) or viral (TLR3, TLR8) products has been proposed to enhance the release of thymic stromal lymphopoietin (TSLP), an IL-7-like cytokine, by airway epithelial cells than activates resident dendritic cells to prime Th2 immune responses (Han et al, 2012;Lee and Ziegler, 2007). Aberrant interactions of TLRs (TLR2, TLR3) with bacterial (peptidoglycan) or viral (rhinovirus) components has been shown to drive degranulation of mast cells and release of muscleconstricting mediators such as leukotrienes and histamine as well as increased production of Th2 cytokines, ultimately resulting in airway narrowing and sustained inflammation (Varadaradjalou et al, 2003).…”
Section: Asthmamentioning
confidence: 99%